Components of cognitive integration between professor and university student in developing university education and Self-education (Journal of the College of Basic Education, 2026)
In light of the tremendous cognitive development witnessed by the world, the development of communication and educational means, and the technological development in the field of education, it has become possible to deliver educational materials to students in easier ways than before in terms of quantity and quality, but the presence of the guiding, mentoring, follow-up and evaluating teacher cannot be ignored or dispensed with; therefore, this research came to clarify the role of both the teacher and the student in self-education, and what the teacher can offer the student? What is the student’s duty towards the teacher? This is what the research answers in two chapters, and each chapter has three demands, and God is the Grantor of success and guidance.